Suspended-sediment dynamics in the tidal reach of a San Francisco Bay tributary - Gregory G. Shellenbarger; Maureen A. Downing-Kunz; David H. Schoellhamer (Ocean Dynamics, 2015)

Erratum to: Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

Flow effects on benthic grazing on phytoplankton by a Caribbean reef - Stephen G. Monismith; Kristen A. Davis; Gregory G. Shellenbarger; James L. Hench; Nicholas J. Nidzieko; Alyson E. Santoro; Matthew A. Reidenbach; Johanna H. Rosman; Roi Holtzman; Christopher S. Martens; Niels L. Lindquist; Melissa W. Southwell; et al. (Limnology and Oceanography, 2010)
We present measurements of flows and fluxes of phytoplankton to Conch Reef, Florida, a Caribbean reef dominated by sponges and soft corals, located in 15 m of water offshore of Key Largo. Vertical profiles of chlorophyll a, a proxy for phytoplankton biomass, showed a near‐bed depletion, indicating the existence of concentration boundary layers. Along with simultaneous measurements of velocity profiles, near‐bed turbulence, and temperature stratification, these profiles were used to compute α, the mass transfer velocity of phytoplankton to the bed (i.e., the flux to the bed normalized by near‐bed concentration). The α value ranged from ‐40 to +130 m d −1 , with a significant linear positive relationship with shear velocity. The median value of α = 48 ± 20 m d −1 is larger than would be expected, given the observed population of filter‐feeding sponges. Nonetheless, these large values of a are consistent with values found recently for another coral reef as well as for a soft bottom estuarine community. Taken as a whole, these measurements indicate that reefs with large roughness and/or energetic currents should be able to support higher biomasses of benthic organisms than would low relief reefs or reefs in sluggish waters.

Measuring sediment accretion in early tidal marsh restoration - John Y. Takekawa; Isa Woo; Nicole D. Athearn; Scott Demers; Rachel J. Gardiner; William M. Perry; Neil K. Ganju; Gregory G. Shellenbarger; David H. Schoellhamer (Wetlands Ecology and Management, 2010)

The importance of submarine groundwater discharge to the near shore nutrient supply in the Gulf of Aqaba (Israel) - Gregory G. Shellenbarger; Stephen G. Monismith; Amatzia Genin; Adina Paytan (Limnology and Oceanography, 2006)
We used two short‐lived radium isotopes ( 223 Ra, 224 Ra) and a mass balance approach applied to the radium activities to determine the nutrient contribution of saline submarine groundwater discharge to the coastal waters of the northern Gulf of Aqaba (Israel). Radium isotope activities were measured along transects during two seasons at a site that lacked any obvious surficial water input. An onshore well and an offshore end member were also sampled. For all samples, nutrients and salinity data were collected. Radium isotope activities generally decreased with distance offshore and exhibited significant tidal variability, which is consistent with a shorederived tidally influenced source. Submarine groundwater contributes only 1–2% of the water along this coast, but this groundwater provides 8–46% of the nutrients. This saline groundwater is derived predominately from tidally pumped seawater percolating through the unconfined coastal aquifer and leaching radium and nutrients. This process represents a significant source of nutrients to the oligotrophic nearshore reef.